Final Consonant Clusters in Azeri Turkish - Razavian, Hossein; Ghalkhani, Omid (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2024)
This article focuses on the analysis of final consonant clusters in Azeri. By consulting two Turkish-Persian dictionaries containing over 100,000 words, the study identifies words with consonant clusters in their syllable structure, specifically (C)VCC or CVCVCC. The research addresses two main questions: the composition of consonant clusters in a syllable coda and the vowels used as the nucleus in (C)VCC structures in Azeri. The data reveals that /æ/ is the predominant vowel in the nucleus of (C)VCC syllables, while /r/ emerges as the most common initial consonant in final clusters. Notably, /t/ is frequently found in post-final positions within the coda. Key findings include the prevalence of /æ/ as the primary vowel in (C)VCC syllables, with /ɑ/, /i/, and /y/ following. Loanwords predominantly feature /e/ in conjunction with /j/ clusters, while /œ/ and /e/ are less prevalent as nucleus vowels. Consonant clusters like /r/, /l/, and /n exhibit versatility with various vowels, whereas other clusters are more selective. The study underscores the unique order of consonant occurrence and combination in the final cluster of (C)VCC syllables in Azeri, highlighting /æ/ as the most active nucleus vowel. Additionally, it emphasizes the mutual relationship between the nucleus and coda in (C)VCC syllables.